“ISLAMIC GUIDING BOOK” Mata Kuliah Agama sebagai Upaya Penanaman Nilai Karakter Jujur dan Disiplin Beribadah Mahasiswa Universitas Wiraraja - Imam Hanafi; Eko Adi Sumitro (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2020)
This study aims to look at several things related to student religious activities as outlined in the book